2007
DOI: 10.1002/pmic.200700215
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression in two human‐derived cell lines exposed in vitro to a 1.9 GHz pulse‐modulated radiofrequency field

Abstract: There is considerable controversy surrounding the biological effects of radiofrequency (RF) fields, as emitted by mobile phones. Previous work from our laboratory has shown no effect related to the exposure of 1.9 GHz pulse-modulated RF fields on the expression of 22,000 genes in a human glioblastoma-derived cell-line (U87MG) at 6 h following a 4 h RF field exposure period. As a follow-up to this study, we have now examined the effect of RF field exposure on the possible expression of late onset genes in U87MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…In addition, the data are very heterogeneous, making any comparison difficult. Several publications showed no significant difference between sham or exposed cells [Gurisik et al, 2006;Qutob et al, 2006;Whitehead et al, 2006a;Chauhan et al, 2007;Huang et al, 2008], or described weak changes that were not confirmed by RT-PCR validation [Zeng et al, 2006;Paparini et al, 2008;Roux et al, 2011;Sakurai et al, 2011], while other microarray studies reported modified gene expression after radiofrequency exposure [Belyaev et al, 2006;Nylund and Leszczynski, 2006;Remondini et al, 2006;Zhao et al, 2007;Huang et al, 2008]. However, these positive studies reported a small number of responsive genes (9-34) with a FC generally close to, or lower than 2.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the data are very heterogeneous, making any comparison difficult. Several publications showed no significant difference between sham or exposed cells [Gurisik et al, 2006;Qutob et al, 2006;Whitehead et al, 2006a;Chauhan et al, 2007;Huang et al, 2008], or described weak changes that were not confirmed by RT-PCR validation [Zeng et al, 2006;Paparini et al, 2008;Roux et al, 2011;Sakurai et al, 2011], while other microarray studies reported modified gene expression after radiofrequency exposure [Belyaev et al, 2006;Nylund and Leszczynski, 2006;Remondini et al, 2006;Zhao et al, 2007;Huang et al, 2008]. However, these positive studies reported a small number of responsive genes (9-34) with a FC generally close to, or lower than 2.…”
Section: Discussionmentioning
confidence: 80%
“…The expression of hsp70 mRNA in radiofrequency exposed groups was due to the effect of non thermal, non ionizing radiation fields as no expression of such gene was observed in unexposed groups which was incubated at 37 O C. The expression of hsp70 gene was well the stress gene hsp70 upon in vitro culture of lymphocytes of both the breeds as compared to higher RF documented in human glioblastoma derived celllines (U87MG) in response to exposure of radiofrequency field (Chauhan et al, 2007). In the present study, lower radiofrequency exposure (850 MHz) caused early expression of exposure (1200 MHz) indicating lower RF exposure was more stressful to immune effector cells especially on peripheral lymphocytes.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, Whitehead et al (2006aWhitehead et al ( , 2006b, Qutob et al (2006), Hirose et al (2006), Zeng et al (2006), and Chauhan et al (2007a) employed high-throughput DNA microarrays to assess global gene expression patterns in exposed cell lines and found no evidence that RF radiation at different frequencies could alter gene expression. Whitehead et al (2006b), Qutob et al (2006), and Chauhan et al (2007a) emphasized that there is a high chance of false positives using such highthroughput techniques because of the large number of genes tested.…”
Section: Gene Expressionmentioning
confidence: 88%
“…Whitehead et al (2006b), Qutob et al (2006), and Chauhan et al (2007a) emphasized that there is a high chance of false positives using such highthroughput techniques because of the large number of genes tested. It was pointed out that it is important to use repeated RF exposures with matched shams, a sham versus sham analysis, and a comparison to a matched control in order to properly account for biological variability where normal fluctuations in gene expression levels are known to occur.…”
Section: Gene Expressionmentioning
confidence: 97%